ANALISIS DAMPAK SOSIAL MEDIA TERHADAP INTERAKSI SOSIAL PADA REMAJA - Indriani Indriani; Intan Tria Rahayu, Jihan Fadhilah, Moly Santya, Ines Tasya Jadidah (CV. ADIBA AISHA AMIRA, 2025)
Social media is a means of social interaction online. So this social media is an electronic media that allows people to create and disseminate content to the public. With the various conveniences provided by this social media, of course social media also has a bad impact on our lives, therefore it is very important for us to understand and sort out how social media works so that we can use it well and avoid the negative impacts of this social media. At the beginning of the emergence of social media was considered as a communication medium used for socializing. This development makes it very easy for people to get information and communicate well with relatives, friends and people without time and distance limits. The convenience provided by social media also makes technological advances increasing. The use of information technology can facilitate the process of finding information. The role of parents in supervising and reminding their children when playing social media is very important so that unwanted things do not happen.